2013
DOI: 10.1182/blood-2012-04-426734
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells are strong promoters of acute ischemic stroke in mice by inducing dysfunction of the cerebral microvasculature

Abstract: Key Points• Regulatory T cells are promoters of ischemic stroke by inducing dysfunction of the cerebral microvasculature. We have recently identified T cells as important mediators of ischemic brain damage, but the contribution of the different T-cell subsets is unclear. Forkhead box P3 (FoxP3)-positive regulatory T cells (Tregs) are generally regarded as prototypic antiinflammatory cells that maintain immune tolerance and counteract tissue damage in a variety of immune-mediated disorders. In the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
293
5
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 305 publications
(316 citation statements)
references
References 56 publications
10
293
5
5
Order By: Relevance
“…32 We found no increase in CD4 þ CD25 þ T cells, which includes activated CD4 þ T cells and Tregs, at 3 hours after pMCAO, but a marked increase in these cells in the ischemic hemisphere 24 hours after either pMCAO or tMCAO. A 10-fold increase in Treg cells was recently reported at 14 days after tMCAO.…”
Section: Numbers Of Cd4mentioning
confidence: 78%
“…32 We found no increase in CD4 þ CD25 þ T cells, which includes activated CD4 þ T cells and Tregs, at 3 hours after pMCAO, but a marked increase in these cells in the ischemic hemisphere 24 hours after either pMCAO or tMCAO. A 10-fold increase in Treg cells was recently reported at 14 days after tMCAO.…”
Section: Numbers Of Cd4mentioning
confidence: 78%
“…For PLT depletion, PLT-depleting serum (10 mL in PBS, IP) or control serum was applied 24 hours before tMCAO. 42 For depletion of macrophages, clodronate liposomes or control liposomes were injected into mice as described before. 37 Furthermore, in some experiments, GPIIb-IIIa was inhibited to prevent intravascular thrombosis by injection of 100 mg anti-GPIIb-IIIa F(ab) 2 or control IgG as described before.…”
Section: Stroke Modelmentioning
confidence: 99%
“…While Treg conferred neuroprotection in certain experimental stroke models [63], they did not seem to affect the neurological outcome in other studies [64]. Furthermore, some studies highlighted the deleterious function of Tregs in acute stroke by inducing dysfunction of the cerebral microvasculature [71], also after Treg boosting with CD28 superagonist [72]. However in other studies, a neuroprotective role of Tregs was observed when these cells were expanded with CD28 superagonist [73], after inhibiting histone deacetylases [74], or after Treg adoptive transfer [74][75][76].…”
Section: Neural Antigens In Strokementioning
confidence: 99%